Disasters Causing the Displacement of Settlements in the North of the Erzincan Plain: Flood, Overflow, and Mudflow - Uysal, Ahmet; Sunkar, Murat (Ankara University, 2022)
Most of the flood and overflow events in Erzincan are seen around the plain and an increase in the frequency of these events has been observed in recent years. Floods and overflows, especially seen in the north of the plain, occur in the form of mudflows, unlike those seen throughout Turkey. Mudflows can cause more loss of life and property compared to floods and overflows. Because of this situation, the relations between the establishment place of the settlements in the north of the plain and flood, overflow and mudflows are examined within the scope of this study. Erzincan Plain is located on the North Anatolian Fault Zone (NAFZ) and is a tectonic plain formed due to the movement of this fault. Streams, which take their source from mountainous areas, form wide deposits in the area where they open to the plain. Depending on the presence of water resources, the settlements are built on these fans. Floods, overflows and mudflows occur on the fans due to the geological, geomorphological and climatic characteristics of the Esence Mountains, which form the source area. These events occur after torrential rain and snowmelt in the source area. Mudflows with flood and overflow are seen in almost all of the rivers in the north of the plain. These naturally occurring events caused disasters in the villages of Buğdaylı, Büyük Çakırman, Günebakan, Geyikli, Çadırtepe, Bayırbağ and Üzümlü from time to time. Mudflows in the north of the plain also threaten the roads and agricultural lands outside the settlement. The occurrence of disasters in these settlements after heavy rains indicates that they were established in high-risk regions. According to disaster data, morphometric analysis results and field observations, all of the settlements located in the north of the plain were established in areas with high sensitivity to floods, overflows and mudflows. Considering the high disaster risk and the situation of being affected by the disaster, some of the relevant settlements have been relocated. Despite this, existing risks continue in some settlements. © 2022, Ankara University. All rights reserved.
Erzincan Ovası Kuzeyindeki Yerleşmelerin Yer Değiştirmesine Neden Olan Afetler: Sel, Taşkın ve Çamur Akmaları
Keywords: Disaster risk; Erzincan Plain; Flood; Overflow and Mudflow; Settlement